Cognitive impairment and microvascular function in end‐stage renal disease. Issue 2 (15th March 2022) - Angermann, Susanne; Günthner, Roman; Hanssen, Henner; Lorenz, Georg; Braunisch, Matthias C.; Steubl, Dominik; Matschkal, Julia; Kemmner, Stephan; Hausinger, Renate; Block, Zenonas; Haller, Bernhard; Heemann, Uwe; et al.
Abstract: Objective: Hemodialysis patients show an approximately threefold higher prevalence of cognitive impairment compared to the age‐matched general population. Impaired microcirculatory function is one of the assumed causes. Dynamic retinal vessel analysis is a quantitative method for measuring neurovascular coupling and microvascular endothelial function. We hypothesize that cognitive impairment is associated with altered microcirculation of retinal vessels. Methods: 152 chronic hemodialysis patients underwent cognitive testing using the Montreal Cognitive Assessment. Retinal microcirculation was assessed by Dynamic Retinal Vessel Analysis, which carries out an examination recording retinal vessels' reaction to a flicker light stimulus under standardized conditions. Results: In unadjusted as well as in adjusted linear regression analyses a significant association between the visuospatial executive function domain score of the Montreal Cognitive Assessment and the maximum arteriolar dilation as response of retinal arterioles to the flicker light stimulation was obtained. Conclusion: This is the first study determining retinal microvascular function as surrogate for cerebral microvascular function and cognition in hemodialysis patients. The relationship between impairment in executive function and reduced arteriolar reaction to flicker light stimulation supports the involvement of cerebral small vessel disease as contributing factor for the development of cognitive impairment in this patient population and might be a target for noninvasive disease monitoring and therapeutic intervention.